Radio Subcarrier Multiplexing in Conjunction with Optical Mode Division Multiplexing for 5G Networks - Angela Amphawan; Baseem Khalaf; Wanasiah Tahir; Hafiza Haron; Rukhiyah Adnan (IAES Indonesia Section, 2015)
5G is speculated to transform the mobilecommunications landscape by increasing data rates, latency,coverage and energy efficiency. Radio-over-fiber (RoF) provides ahigh-capacity, efficient and scalable 5G architecture fortransporting radio signals through optical fibers, exploiting theenormous bandwidth of the optical fiber cables. In this paper, anew radio-over-fiber (RoF) architecture for future 5G networks isproposed using SCM-MDM for converging data streams fromdifferent picocells. Different sets of the Hermite-Gaussian (HG)modes are introduced for the SCM-MDM system in RoF. The effectof different sets of HG modes on the RoF system performance arecompared in terms of the transverse electric fields, eye diagrams,modal analyses and bit-error rates. A total throughput of 19.5 Gb/sis achieved